Antioxidant and hepatoprotective effect of aqueous extract of germinated and fermented mung bean on ethanol-mediated liver damage - Mohd Ali, Norlaily; Mohd Yusof, Hamidah; Long, Kamariah; Yeap, Swee Keong; Ho, Wan Yong; Beh, Boon Kee; Koh, Soo Peng; Abdullah, Mohd Puad; Mohammed Alitheen, Noorjahan Banu (Hindawi Publishing Corporation, 2013)
Mung bean is a hepatoprotective agent in dietary supplements. Fermentation and germination processes are well recognized to enhance the nutritional values especially the concentration of active compounds such as amino acids and GABA of various foods. In this study, antioxidant and hepatoprotective effects of freeze-dried mung bean and amino-acid- and GABA-enriched germinated and fermented mung bean aqueous extracts were compared. Liver superoxide dismutase (SOD), malondialdehyde (MDA), ferric reducing antioxidant power (FRAP), nitric oxide (NO) levels, and serum biochemical profile such as aspartate transaminase (AST), alanine transaminase (ALT), triglycerides (TG), and cholesterol and histopathological changes were examined for the antioxidant and hepatoprotective effects of these treatments. Germinated and fermented mung bean have recorded an increase of 27.9 and 7.3 times of GABA and 8.7 and 13.2 times of amino acid improvement, respectively, as compared to normal mung bean. Besides, improvement of antioxidant levels, serum markers, and NO level associated with better histopathological evaluation indicated that these extracts could promote effective recovery from hepatocyte damage. These results suggested that freeze-dried, germinated, and fermented mung bean aqueous extracts enriched with amino acids and GABA possessed better hepatoprotective effect as compared to normal mung bean.